Pemberdayaan Ibu Hamil Tentang Senam Hamil Melalui Pelayanan Home Care di Kabupaten Bulukumba - Erniawati Erniawati; Ariani Ariani; Ermawati Ermawati; Susilawati Susilawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Pregnancy exercise is a movement therapy therapy given to pregnant women to prepare themselves both physically and mentally for childbirth. Pregnancy exercise is needed by every pregnant woman, because it can make the body fit and healthy, and able to carry out daily activities, so that stress due to anxiety before giving birth can be minimized. However, many pregnant women do not do pregnancy exercise because they are unsure and afraid of their pregnancy if they do pregnancy exercise. Pregnancy exercise exercises that are carried out regularly both at the gym and at home in their spare time can lead pregnant women towards a physiological delivery as long as there are no pathological conditions accompanying the pregnancy. The purpose of Community Service in the Work Area of the Caile Health Center is to increase the ability of pregnant women and cadres to practice pregnancy exercises, so that they will increase the knowledge and health of pregnant women and prepare for childbirth. This community service activity begins with training for existing Posyandu cadres, providing supporting facilities and infrastructure in the form of leaflets and modules for pregnant women exercise, and doing pregnancy exercises in home care. The results of this Community Service activity are the formation of pregnancy exercise cadres, pregnant women can practice pregnancy exercise at home, as well as the provision of facilities and infrastructure in the form of leaflets and pregnancy exercise modules